Characterisation of the radio frequency spectrum emitted by high energy air showers with LOFAR - Rossetto, L.; Bonardi, A.; Buitink, S.; Corstanje, A.; Falcke, H.; Hare, B. M.; Hörandel, Jörg R.; Mitra, P.; Mulrey, K.; Nelles, Anna; Olid Gonzalez, A.; Rachen, J. P.; et al. (Proceedings of Science, 2017)
The high number density of radio antennas at the LOFAR core in Northern Netherlands allows to detect radio signals emitted by extensive air showers in the energy range 1016 - 1018 e V, and to characterise the geometry of the observed cascade in a detailed way. The radio signal emitted by extensive air showers along their propagation in the atmosphere has been studied in the 30 - 70 MHz frequency range. The study has been conducted on real data and simulated showers. Regarding real data, cosmic ray radio signals detected by LOFAR since 2011 have been analysed. For simulated showers, the CoREAS code, a plug-in of the CORSIKA particle simulation code, has been used. The results show a clear dependence of the frequency spectrum on the distance to the shower axis for both real data and simulations. In particular, the spectrum flatten at a distance around 100 m from the shower axis, where the coherence of the radio signal is maximum. This behaviour could also be used to reconstruct the position of the shower axis at ground. A correlation between the frequency spectrum and the geometrical distance to the depth of the shower maximum Xmax has also been investigated. The final aim of this study is to find a method to improve the inferred information of primary cosmic rays with radio antennas, in view of affirming the radio detection technique as reliable method for the study of extensive air showers.
CRIS-Team Scopus Importer:2023-08-15